La Fauna Silvestre De Córdoba Y Su Rol Ecológico Aplicadas En Prácticas Socio-Comunitarias De Enseñanza - Dellafiore, Claudia. M.; Autrán, Valeria; Aiassa, Delia; Brandolin, Pablo (European Scientific Journal, ESJ, 2016)
The National Rio Cuarto University (UNRC, Cordoba, Argentina) has a scheme to encourage the inclusion of community-engagement activities (PSC) in the Higher Education curriculum. In this context, the Natural Sciences department (Faculty of Exact Sciences, Physico-Chemical and Natural) carried out a PSC activity named “Animal Biodiversity”. This activity responds to specific needs by the local teaching community and the general public, where many teachers admit that they lack knowledge about the local fauna and their ecological role, and that they don’t have enough time or information to develop this type of content during their scheduled teaching sessions. Therefore, the present activity aimed to liaise the Higher Education community and local primary and secondary school teachers. Biology university students taking the “Systematic Zoology” module prepared a session about “Snakes and scorpions of Cordoba. Their identification and ecological role” that included both theoretical and practical aspects for secondary school students from “Ramón Artemio Estafolani – Granja Siquem” school. The analysis of the PSC activities highlighted the importance of building inclusion bridges with the local community, and the need to build social and cultural support networks. It is important to implement processes that encourage PSC in Higher Education, in order to highlight professional values, promote social responsibility and develop creative, active and supportive thinking. It would also provide comprehensive training of university students in ways that meet the demands and challenges of society. This work stresses the need for PSC to be continued in time by including them in our Higher Education curriculum.